Public Debt Indexation and Denomination : The Case of Brazil - Goldfajn, Ilan (IMF Working Papers; Working Paper, 1998)
The paper models the optimal debt management strategy of the public sector when issuing nominal, price-level-indexed and foreign-denominated debt securities. The model predicts that the variance of inflation, the size of the public debt, the variance of the real exchange rate, and the correlation of inflation with public expenditures are the main determinants of public debt management. Using this framework, the paper analyzes the Brazilian experience with indexed debt in the last decade. In particular, it explains the large increase of indexed public debt in Brazil prior to the 1994 Real plan and, thereafter, the steady decline in its use.